Frühe Reisende in Phokis und Lokris Berichte aus Zentralgriechenland vom 12. bis 19. Jahrhundert - Felsch-Klotz, Annamarie (Universitätsverlag Göttingen, 2009)
Today, detailed reports of travellers, traders and diplomats are interesting and often pleasurable sources for the conditions in Central Greece. This book shows how the landscapes of Phokis and Lokris changed in the medieval age and during the Ottoman regency. It also pictures how Greece changed from the time of the Kingdom to the present-days.